Analisa current ratio, net profit margin, total asset turnover, dan debt to equity ratio terhadap kinerja keuangan pada perusahaan infrastruktur, ultilitas dan transportasi yang terdaftar di Bursa Efek Indonesia periode 2018-2020 - Veronika Siregar, Ulina; Sembiring, Luciana Grace; Manurung, Leonita; Nasution, Siti Aisyah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the Current Ratio, Net Profit Margin, Total Asset Turnover, and Debt to Equity Ratio to Financial Performance. The population in this study are 45 Infrastructure, Utilities and Transportation companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique is purposive sampling. Analysis of data with multiple linear regression using SPSS 20 Software, the results of this study indicate that the current ratio partially has no effect and is not significant on financial performance, net profit margin partially and significantly affects financial performance, total asset turnover partially and significantly affects financial performance. Financial performance, Debt To Equity Ratio partially has a negative and significant effect on financial performance while simultaneously current ratio, net profit margin, total asset turnover, Debt To Equity Ratio has a positive and significant effect on financial performance. The coefficient of determination is 0.872 which means it is worth 87.2% of the variables are Current Ratio, Net Profit Margin, Total Asset Turnover, and Debt to Equity Ratio while the remaining 12.8% is influenced by other variables.